Experimental Study on the Feasibility of Using Water Glass and Aluminum Sulfate to Treat Complications in High Liquid Limit Soil Subgrade - Wen-hui Zhang; Hua-wen Zheng; Jia-wei Qi; Bao-tian Wang (Advances in Materials Science and Engineering)
The feasibility of using water glass and aluminum sulfate to treat high liquid limit soil subgrade diseases is studied through laboratory experiments, and the following results were observed. After improving the high liquid limit clay with water glass and aluminum sulfate, the liquid limit decreases, the plastic limit increases, and the plasticity index decreases. Compared with untreated soil, the clay content of the improved soil decreases, while the silt and coarse contents increase. The absolute and relative expansion rates of the improved soil are both lower than those of the untreated soil. With the same number of dry and wet cycles, the decreased degrees of cohesion and internal friction angle of the improved soil are, respectively, one-half and one-third of those of the untreated soil. After three dry and wet cycles, the California bearing ratio (CBR) of the untreated soil does not meet the requirements of specifications. However, after being cured for seven days and being subjected to three dry and wet cycles, the CBR of the improved soil, with 4% water glass solution and 0.4% aluminum sulfate, meets the requirements of specifications.